2010
DOI: 10.1001/archoto.2010.175
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout Among Microvascular and Reconstructive Free-Flap Head and Neck Surgeons in the United States

Abstract: Most MVFF surgeons experience moderate professional burnout secondary to moderate EE and DP. This may be a problem of proper balance between professional obligations and personal life goals. Most MVFF surgeons, nonetheless, experience a high level of personal accomplishment in their profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 21 publications
2
43
1
1
Order By: Relevance
“…However, almost one-quarter of the sample reported high levels of emotional exhaustion, suggesting that a portion of Polytrauma team members may be at risk for burnout. The levels of emotional exhaustion found with this sample are consistent with levels reported in studies of surgeons [27][28][29] and mental health providers [15], but lower than levels of emotional exhaustion reported by a large sample of US nurses [30]. Levels of depersonalization or cynicism were lower (M ¼ 3.55 AE 4.29) than those reported in a sample of 1400 social service workers (M ¼ 9.4 AE 6.9) [26] as well as in a study of 1200 psychologists [31] (M ¼ 5.21 AE 4.26), indicating that participants in this study derived significant meaning from their work.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, almost one-quarter of the sample reported high levels of emotional exhaustion, suggesting that a portion of Polytrauma team members may be at risk for burnout. The levels of emotional exhaustion found with this sample are consistent with levels reported in studies of surgeons [27][28][29] and mental health providers [15], but lower than levels of emotional exhaustion reported by a large sample of US nurses [30]. Levels of depersonalization or cynicism were lower (M ¼ 3.55 AE 4.29) than those reported in a sample of 1400 social service workers (M ¼ 9.4 AE 6.9) [26] as well as in a study of 1200 psychologists [31] (M ¼ 5.21 AE 4.26), indicating that participants in this study derived significant meaning from their work.…”
Section: Discussionsupporting
confidence: 89%
“…No significant differences in participant characteristics for any of the MBI-HSS sub-scales (emotional exhaustion, depersonalization and personal accomplishment) were found for age category, race, years in practice, years at VA, primary role or percentage of time providing direct care. These findings are in contrast to previous studies which showed that higher levels of burnout are correlated with younger age and fewer years in practice [33], but similar to a recent study demonstrating no relationships between burnout and age [27]. These inconsistencies may be related to organizational differences, roles of the providers, sample size and/ or training and educational efforts directed to providers.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Traditionally, free tissue transfer has been seen as extraordinarily demanding with regard to time and resources. It is thus unsurprising that microvascular surgeons experience high rates of burnout 5. However, with increasing surgical volume and institutional experience, free flap reconstruction at our institution and in other high‐volume programs has transitioned from an extraordinary to a frequent and somewhat ordinary procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, long-term complications have been described such as fatigue, boredom and professional burnout [4,21,22,23]. Indeed, mild mental stress associated with increased HR has been related to sudden death in the general population [24].…”
Section: Introductionmentioning
confidence: 99%